2007
DOI: 10.1097/01.tp.0000287967.54222.4d
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the Survival Rate by Fetal Liver Cell Transplantation in a Mice Lethal Liver Failure Model

Abstract: The transplanted cells were engrafted and repopulated the liver of recipient mice, resulting in the improvement of the survival rate of the liver injury model mice. We therefore propose that HPCs are a desirable cell source for cell transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…The DT receptor has been identified as a membrane‐anchored form of the HB‐EGF precursor . Recently, it was shown that transplanted hepatic progenitor cells derived from the fetal liver were efficiently engrafted and repopulated in the liver of recipient HB‐EGF‐expressing mice with DT stimulation . Using this model, efficient engraftment of the transplanted cells in recipient mice with HB‐EGF expression in the liver enabled us to examine the fate of transplanted hepatic progenitor cells with constitutive AID expression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The DT receptor has been identified as a membrane‐anchored form of the HB‐EGF precursor . Recently, it was shown that transplanted hepatic progenitor cells derived from the fetal liver were efficiently engrafted and repopulated in the liver of recipient HB‐EGF‐expressing mice with DT stimulation . Using this model, efficient engraftment of the transplanted cells in recipient mice with HB‐EGF expression in the liver enabled us to examine the fate of transplanted hepatic progenitor cells with constitutive AID expression.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the actively transcribed genes in the liver‐lineage cells preferentially accumulated SNVs and might contribute to the development of tumor cells. However, based on the model used in our study, we could not fully determine whether the developed tumors derived directly from the fetal hepatic progenitor cells or via mature hepatocytes, because the transplanted fetal progenitor cells differentiated into mature hepatocytes in the recipient liver . Moreover, the truly significant driver mutations responsible for hepatocarcinogenesis remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The adult primary hepatocytes were used commonly in experimental and pre-clinical studies(26). These cells include allogeneic, xenogeneic or autologus primary isolated hepatocytes.…”
Section: Types Of Cells For Transplantation In Liver Diseasesmentioning
confidence: 99%